Fish diversity in the Pantanos de Centla biosphere reserve - Alvarez-Pliego, Nicolás; Sánchez, Alberto J.; Florido-Araujo, Rosa Amanda; Salcedo-Meza, Miguel Ángel; Cruz-Ramírez, Allan K-; Barba-Macias, Everardo (Ecosistemas y Recursos Agropecuarios, 2021)
The systematic list of ﬁsh collected during 2014 and 2015 in the Pantanos de Centla Biosphere Reserve registered a 25% increase in the previous diversity records, mainly due to the presence of diadromous ﬁsh. The checklist included 75 species, accounting for 37% of the ichthyofauna in the Grijalva- Usumacinta basin. Among the ﬁve invasive non-native species, the armored catﬁsh (Pterygoplichthys spp.) registered the maximum frequency of capture. Moreover, 48 migratory species were identiﬁed (38 diadromous and 10 potamodromous). The dominance of diadromous ﬁsh and their presence in both lagoons and rivers indicated the conservation of the hydraulic interconnection between rivers and lagoons. In the sampling, the absence of seven freshwater species, that were common in previous publications was observed. The above may be due to the decrease in habitats as a consequence of human activities and the introduction of invasive species. This study highlights the need for further studies focused on the ﬁsh biology, mainly to clarify the potamodromous condition and understand the lateral migration that some species present during their ontogeny.